Thinking Skills, Reading Comprehension, and Working Memory in Normal-School Students - Esquivel-Gámez, Ismael (2022)
Objective. This work aimed to evaluate thinking skills, reading comprehension, and working memory in pre-service teacher students from Veracruz, Mexico, and analyze the possible relationships between them, in order to have the bases to prevent possible deficiencies and correct them from the teacher training stage. Methodology. It is a study with a quantitative approach and a descriptive, cross-sectional, observational, and prospective design in which 45 students from two institutions in the area participated. Different tests and a Likert scale with 19 items were used to measure thinking skills. For reading comprehension, a cloze-type test was used; and for working memory in its verbal and visuospatial domain, complex span tasks were used. Results analysis. Serious deficiencies in thinking skills were found. Those corresponding to inductive verbal and figurative reasoning had a positive and significant association with some verbal and visuospatial working memory measures. Furthermore, the reading comprehension level was low and positively associated with thinking skills tests requiring little or no reading effort. Conclusions. Firstly, this work allows recognizing the worrying condition of future teachers of children in basic cognitive skills. Secondly, it proposes ways of developing thinking skills through training working memory and strengthening comprehension reading and vocabulary.